2017
DOI: 10.1159/000457881
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fluvastatin on Reproductive Function in Obese Male Rats Induced by High-Fat Diet through Enhanced Signaling of mTOR

Abstract: Background: Statins can reduce reproductive damage induced by obesity or high-fat diet (HFD), but the specific regulatory mechanisms are largely unknown. Since mTOR/p70s6k sinaling promotes spermatogonia proliferation and spermatogenesis, we hypothesized that this pathway will be involved in the protective effects of statin in HFD-induced reproductive dysfunction. Methods: Male Sprague Dawley rats (3 weeks old) were randomly divided into a control group (standard diet), HFD group, and a fluvastatin group (HFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…It has been shown that HFD altered the carbohydrate metabolism, the testicular architecture and leads to spermatogenetic damage and impaired the fertility. 6,18,19 In the present study, serum testosterone, was comparable between normal diet and HFD animals, this in consent with Fernandez et al who observed analogous testosterone levels in HFD rats compared with standard chow fed rats. 20 Serum testosterone depletion accompanied with a reduction of sexual organ weight was observed in rats that fed on hypercaloric diet.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that HFD altered the carbohydrate metabolism, the testicular architecture and leads to spermatogenetic damage and impaired the fertility. 6,18,19 In the present study, serum testosterone, was comparable between normal diet and HFD animals, this in consent with Fernandez et al who observed analogous testosterone levels in HFD rats compared with standard chow fed rats. 20 Serum testosterone depletion accompanied with a reduction of sexual organ weight was observed in rats that fed on hypercaloric diet.…”
Section: Discussionsupporting
confidence: 92%
“…Statins also affect the proliferation of tumor cells in murine models of breast, colon, pancreatic, liver, and prostate cancers [47–50]. Additionally, statins can also stimulate inflammatory responses and anticancer immune surveillance via the phosphorylation of Akt and down-regulation of the mammalian target of rapamycin (mTOR) [51]. …”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, reduced weight gain has been reported in high-fat diet-fed rats given fluvastatin, and this was also not concluded to be an adverse effect. 47 Accordingly, the lower body mass observed in the SIM-treated groups in the present study is not considered to be pathological.…”
Section: Discussionmentioning
confidence: 52%